Mapping the impacts of food aid: Current knowledge and future directions - Amy Margolies; John Hoddinott (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper provides an overview on the impacts of food aid. We consider its effects on consumption, nutrition, food markets and labour supply, as well as the extent to which it exacerbates or mitigates conflict. We also consider the comparative evidence on alternatives to food aid including evidence on cost, impact, relative risks and beneficiary preferences. We note that there are two large gaps in the extant literature: the comparative effects of food and cash assistance at the household level; and the causal links between food aid and conflict.
Keywords: H84; O1; O19; Q18; 330; food aid; humanitarian assistance; social protection; disincentives; conflict; Nahrungsmittelhilfe; Wirkungsanalyse